Phosphoenolpyruvate, a glycolytic intermediate, as a cytoprotectant and antioxidant in ex‐vivo cold‐preserved mouse liver: a potential application for organ preservation. (16th November 2012) - Kondo, Yuki; Ishitsuka, Yoichi; Kadowaki, Daisuke; Fukumoto, Yusuke; Miyamoto, Yohei; Irikura, Mitsuru; Hirata, Sumio; Sato, Keizo; Maruyama, Toru; Hamasaki, Naotaka; Irie, Tetsumi
Abstract Objectives The aim of this study was to examine the effect of phosphoenolpyruvate (PEP), a glycolytic intermediate, on organ damage during cold preservation of liver. Methods An ex‐vivo mouse liver cold‐preservation model and an in‐vitro liver injury model induced by hydrogen peroxide in HepG2 cells were leveraged. Key findings PEP attenuated the elevation of aminotransferases and lactate dehydrogenase leakage during organ preservation, histological changes and changes in oxidative stress parameters (measured as thiobarbituric acid reactive substance and glutathione content) induced by 72 h of cold preservation of the liver. The effects were comparable with the University of Wisconsin solution, a gold standard organ preservation agent. The decrease in ATP content in liver during the cold preservation was attenuated by PEP treatment. PEP prevented the cellular injury and increases in intracellular reactive oxygen species in HepG2 cells. In addition, PEP scavenged hydroxyl radicals, but had no effect on superoxide anion as evaluated by an electron paramagnetic resonance spin‐trapping technique. Conclusions PEP significantly attenuated the injury, oxidative stress and ATP depletion in liver during cold preservation. The antioxidative potential of PEP was confirmed by in‐vitro examination. We suggest that PEP acts as a glycolytic intermediate and antioxidant, and is particularly useful as an organ preservation agent in clinical transplantation.